Budaya Adab Kesantunan Berbahasa Dalam Masyarakat Indonesia - Rohana Rohana; Muhammad Irfan; Rahmawati Patta; Fatun Fatimah Azahrah; Nurilah Fitrah (Seminar Nasional LP2M UNM, 2022)
Abstract. The aim of this research is to describe the realization of language politeness based on (1) maxim of wisdom; (2) language politeness based on generosity maxim; (3) appreciation maxim; (4) simplicity maxim; (5) consensus maxim; and (6) sympathy maxim. The data in this study are the utterances of the general public which are then categorized as polite if they comply with the maxim assessment indicators. The data collection techniques used in this study were observing techniques, note-taking techniques, and data reduction. The analysis techniques used are: 1) identifying the existence of types of politeness maxims in each utterance data; 2) analyze the speech data based on the criteria for assessing language politeness from Leech's theory; and 4) describe the results of speech data analysis. The results of the study show that there are speeches that comply with Leech's politeness maxims, and the results of the analysis of the 6th maxim of speech have benefits for the politeness of the speaker and the speech is detailed as follows: Based on the results of the analysis conducted by the researcher, it can be concluded that politeness according to Leech's speech 6 utterances were found consisting of 5 wisdom maxims, 1 generosity maxim, 5 appreciation maxims, 1 modesty maxim, 2 consensus maxims and 2 maxims. The results of the analysis also show violations of the maxims. These violations include violations of the maxim of wisdom, the maxim of generosity, the maxim of modesty, the maxim of agreement, and the maxim of sympathy.  Keywords: Language Politeness Culture, Indonesian Society